The Practicing Level of Formative Evaluation among High School Science Teachers and its methods in teaching science from the point of view of the teachers themselves - Alrasheedi, Nora Samah Lafi; Alahmad, Nidal Shaban (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the practicing Level of Formative Evaluation among high school science teachers and its methods in teaching science from the point of view of the teachers themselves, to achieve the study objectives, the qualitative approach was followed by using the observation card for the practicing of (6) science teachers for six methods of formative evaluation to measure aspects of different learning outcomes. These methods of study included: direct class questions, discussion, assignments and performance tasks, formative tests, observation, and applications. The results of the study showed that the discussion method was the most widely used among the formative evaluation methods, followed by the class questions, and that none of the six teachers used the two methods: observation or practical applications. The practices were common, and the female teachers did not use participatory evaluation methods, and they did not use self-correcting tests except for one parameter, and they did not record any evaluation activities in which peer evaluation was used. The results showed that the level of female teachers’ practices of formative evaluation methods sometimes agreed with their level of knowledge of these methods, and in other times the practices were at a lower level than female teachers’ knowledge of these methods, and the level of secondary school science teachers’ practice of evaluation methods was rarely higher than their knowledge of them. In light of these results, the researcher recommended several recommendations, the most important of which are: training female teachers to practice the methods of formative evaluation, and to include practical applications of formative evaluation within the teacher preparation programs in the faculties of education in Saudi universities.